Codification of Commercial Law in the Principality of Serbia (1849–1860) - Drakić, Gordana; Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The article exposes codification of commercial law in the Principality of Serbia. That process took place between 1849 and 1860. Its first phase, lasting from 1849 to 1853, commenced on Ministry of Finance’s initiative. The comittee consisting of state officials and Belgrade merchants drew up a draft commercial code in 1851. Although the legislative body, State Council, primarily approved of codification, in 1853 it rejected the draft with motivation that the text had not contained the matter of commercial courts, that Serbian people as poorly educated would not be able to understand commercial code’s complicated notions and that Serbian merchants were immature for codified commercial law. Commercial Comittee, the organization founded in January 1856 with the goal of proposing measures aimed to enchance trade in Serbia, requseted for introduction of commercial code the very same year. In the beginning of 1857 the Council formed the comittee tasked with revising the draft from 1851 and preparing drafts on organization of commercial courts and court procedure in commercial matters; all three texts were meant to become parts of commercial code. The composed draft had been sent to Commercial Comittee on 14 February 1859, which sent it back to the Ministry with its remarks on 8 October the same year. After the three-member committee formed by the Ministry of Justice on 24 November 1859 had somewhat altered the draft, the corrected version was consigned to the Prince. Commercial code had received the Prince’s sanction on 22 December 1859 and entered into force on 26 January 1860, thus making Serbia one of the countries with codified commercial law. The cause for the codification doubtlessly lies in the trade between merchants of Belgrade and those from Austria that intensified subsequent to Revolution 1848. In these business relations Austrian merchants were using bills of exchange as security, which meant that their Belgrade partners were to be most punctual in fullfiling their contractual obligations. However, due to lack of commercial regulations and long-lasting civil procedure before Serbian courts, the merchants from the capital could not realize their own claims towards the debtors from the province and were consequently unable to collect money to settle their own debts. For that reason, from 1852 onwards Belgrade merchant were filing petitions for enactment of commercial code. Their petitions had ever more undersigneds, which may indicate that the problem was constantly becoming more serious. Nevertheless, only in the end of 1850s, when the lack of commercial code showed its palpable effects in province, was the code introduced.